Dreams of difference, songs of the same : the musical moment in film - Herzog, Amy (University of Minnesota Press, 2010)
Musical spectacles are excessive and abstract, reconfiguring time and space and creating intense bodily responses. Amy Herzog's engaging work examines those instances where music and movement erupt from within more linear narrative frameworks. The representational strategies found in these films are often formulaic, repeating familiar story lines and stereotypical depictions of race, gender, and class. Yet she finds the musical moment contains a powerful disruptive potential. Dreams of Difference, Songs of the Same investigates the tension and the fusion of difference and repetition in films t.